2014
DOI: 10.1109/tdmr.2013.2281726
|View full text |Cite
|
Sign up to set email alerts
|

Combined MOS–IGBT–SCR Structure for a Compact High-Robustness ESD Power Clamp in Smart Power SOI Technology

Abstract: Smart power technologies are required to withstand high-electrostatic-discharge (ESD) robustness under both powered and unpowered conditions, particularly for automotive and aeronautic applications among many others. They are concurrently confronted to the challenges of high-temperature operation in order to reduce heat-sink-related costs. In this context, very compact high-robustness ESD protections with low sensitivity to temperature are required. To fulfill this need, we studied a new ESD protection structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…This choice can be explained by the fact that the obtained results in the previous silicon run exhibited the maximum and the minimum holding current for the 1P4N and 3P1N respectively, and the best ESD performance for the 1P2N. The results confirmed that the effect of P + diffusion percentage in the drain, corresponding to the IGBT one, has the same effect as shown and explained in [4].…”
Section: Proposed New Solutions and Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…This choice can be explained by the fact that the obtained results in the previous silicon run exhibited the maximum and the minimum holding current for the 1P4N and 3P1N respectively, and the best ESD performance for the 1P2N. The results confirmed that the effect of P + diffusion percentage in the drain, corresponding to the IGBT one, has the same effect as shown and explained in [4].…”
Section: Proposed New Solutions and Resultssupporting
confidence: 77%
“…After carrying out TCAD simulations using Sentaurus Device and based on previous results obtained in [3], [4], [10], three major topological modifications have been applied in order to make this component latch-up compliant:…”
Section: Proposed New Solutions and Resultsmentioning
confidence: 99%
See 3 more Smart Citations